Cost-effectiveness of Simple Insulin Infusion Devices Compared to Multiple Daily Injections in Uncontrolled Type 2 Diabetics in the United States Based on a Simulation Model - Wahlqvist, Peter (J Health Econ Outcomes Res, 2018)
BACKGROUND: As type 2 diabetes (T2D) progresses, administering basal and bolus insulin through multiple daily injections (MDI) is often required to achieve target control, although many people fail to achieve target levels. Continuous subcutaneous insulin infusion (CSII) treatment with traditional pumps has proven effective in this population, but use remains limited in T2D due to CSII cost and complexity. A new class of simple insulin infusion devices have been developed which are simpler to use and less expensive. This paper assesses at what price one such simple insulin infusion device, PAQ(®) (Cequr SA, Switzerland), may be cost-effective compared to MDI in people with T2D not in glycemic control in the United States. METHODS: Published equations were used in a simulation model to project long-term cost-effectiveness over 40 years, combined with data from the recent OpT2mise study, assuming similar efficacy of CSII and simple insulin infusion. Cost-effectiveness was pre-defined in relation to per capita gross domestic product (GDP), where incremental cost-effectiveness ratios below 1X the per capita GDP per quality-adjusted life year (QALY) gained were defined as “highly cost-effective” and below 3X GDP per capita as “cost-effective.” RESULTS: Simple insulin infusion resulted in 0.17 QALYs gained per patient compared to MDI, along with lifetime cost-savings of USD 66 883 per person due to reduced insulin use and less complications. Analyses on price sensitivity of simple insulin infusion indicated that a device such as the PAQ is cost-effective compared with MDI up to price points of around USD 17 per day. CONCLUSIONS: For people with T2D not in glycemic control on MDI, simple insulin infusion devices such as PAQ have the potential to be highly cost-effective in the United States.